Estilos de aprendizaje y rendimiento académico en ´primero de bachillerato de la Unidad Educativa “Santa Mariana de Jesús - Balseca López, María Angélica (2024)
This research aims to explore the relationship between learning styles and academic performance in mathematics among first-year high school students at the "Santa Mariana de Jesús" Educational Unit. The study analysed individual learning preferences that influence the acquisition of mathematical skills. Through a quantitative approach and a non-experimental research design, data were collected using a questionnaire adapted from the Honey-Alonso Learning Styles Questionnaire (CHAEA) to identify predominant learning styles, and students' grades were analysed to determine patterns in academic performance. The results reveal that the predominant learning style is the pragmatic style, which is highly frequent among students, while the active learning style is the least common but presents better grades in mathematics. This suggests that adapting teaching strategies to these styles may improve academic performance. This research concludes that identifying and considering learning styles in the educational process is essential for improving academic outcomes and enhancing students' educational experience